Evolution of novel mimicry rings facilitated by adaptive introgression in tropical butterflies (2017)
Understanding the genetic basis of phenotypic variation and the mechanisms involved in the evolution of adaptive novelty, especially in adaptive radiations, is a major goal in evolutionary biology. Here, we used whole-genome sequence data to investigate the origin of the yellow hindwing bar in the Heliconius cydno radiation. We found modular variation associated with hindwing phenotype in two narrow noncoding regions upstream and downstream of the cortex gene, which was recently identified as a pigmentation pattern controller in multiple species of Heliconius. Genetic variation at each of these modules suggests an independent control of the dorsal and ventral hindwing patterning, with the upstream module associated with the ventral phenotype and the downstream module with the dorsal one. Furthermore, we detected introgression between H. cydno and its closely related species Heliconius melpomene in these modules, likely allowing both species to participate in novel mimicry rings. In sum, our findings support the role of regulatory modularity coupled with adaptive introgression as an elegant mechanism by which novel phenotypic combinations can evolve and fuel an adaptive radiation. © 2017 John Wiley and Sons Ltd